Mapping the literature on social responsibility and stakeholders' pressures in the mining industry - Margarida Rodrigues; Maria do Céu Alves; Rui Silva; Cidália Oliveira (Journal of Risk and Financial Management, 2022)
Mining activities can be good for the local economy, but they can also have a negative impact, which has created increasing pressure from stakeholders. A constructive and positive engagement between a company and its stakeholders is important for sustainability issues and can provide a shared understanding of sustainable development. This review aims to examine the growth trajectory, the most influential documents, and the conceptual framework of the literature on stakeholder engagement and corporate social responsibility (CSR) in the mining industry. Moreover, tries to answer the following research questions: What research streams have been followed? Which theories and research paradigms have been used? A bibliometric analysis was performed using 149 documents extracted from the Web of Science and Scopus databases. The documents obtained were analysed using Bibliometrix software. The results suggest that the most studied constructs within the mining industry are related to sustainability issues, management and legitimacy concerns, and the importance of stakeholders, particularly local communities, and the social impacts that mining generates. The study contributes to the literature by reviewing prominent cited references and documents that cited them, the authors provide the landscapes and research gaps of major research lines for further development.
Keywords: 650; mining industry; corporate social responsibility (CSR); stakeholders; social license to operate; systematic literature review